The Real-Life Effectiveness of Palivizumab for Reducing Hospital Admissions for Respiratory Syncytial Virus in Infants Residing in Nunavut - Anna Banerji; Vladimir Panzov; Michael Young; Bonita E Lee; Muhammad Mamdani; B Louise Giles; Marguerite Dennis; Johanne Morel; Danny Bisson; Bosco A Paes; Charles Hui; Jim Mahony (Canadian Respiratory Journal)
BACKGROUND/OBJECTIVE: Nunavut has the highest hospitalization rates for respiratory syncytial virus (RSV) worldwide, with rates of 166 per 1000 live births per year <1 year of age. Palivizumab was implemented in Nunavut primarily for premature infants, or those with hemodynamically significant cardiac or chronic lung disease; however, the effectiveness of the program is unknown. The objective of the present multisite, hospital-based surveillance study was to estimate the effectiveness of palivizumab in infants <6 months of age in Nunavut for the 2009 and 2010 RSV seasons.